Analysis of Wave, Current, and Surface Wind Conditions on Shipping Safety Risks on the Tanjung Perak - Lembar Ship Route Based on BMKG Data 2024 - Wiratama, Rizki Bagus Panji; Lestari, Nurita Apridiana; Sani, Puteri Permata (Universitas Hang Tuah, 2026)
Maritime safety in Indonesia is highly influenced by oceanographic dynamics such as waves, surface currents, and winds, especially along critical routes like Tanjung Perak–Lembar. However, studies integrating these parameters with recent marine meteorological data for this route remain limited. This study aims to assess seasonal variability in wave height, current speed, and wind conditions in 2024 to evaluate potential risks to navigation. A quantitative approach was applied using secondary data from the BMKG InaWave model, focusing on seven observation points along the route. Analysis was conducted using Python and Excel for spatial mapping and temporal trend visualization. Results show that (1) wind speeds during the southeast monsoon reached 7.14 m/s, contributing to wave heights up to 0.87 meters; (2) surface currents exceeding 100 cm/s were frequently identified in the Lombok Strait; and (3) the combination of strong currents and moderate waves increases safety risks for small vessels and barges. These findings highlight the importance of incorporating updated marine meteorological data in voyage planning and early warning systems. The study contributes to regional maritime safety research and supports practical decision-making for ship operators and port authorities.